The Wittenoom legacy. (31st October 2019) - Musk, Arthur W (Bill); Reid, Alison; Olsen, Nola; Hobbs, Michael; Armstrong, Bruce; Franklin, Peter; Hui, Jennie; Layman, Lenore; Merler, Enzo; Brims, Fraser; Alfonso, Helman; Shilkin, Keith; et al.
Abstract: The Wittenoom crocidolite (blue asbestos) mine and mill ceased operating in 1966. The impact of this industry on asbestos-related disease in Western Australia has been immense. Use of the employment records of the Australian Blue Asbestos Company and records of the Wittenoom township residents has permitted two cohorts of people with virtually exclusive exposure to crocidolite to be assembled and studied. Follow-up of these two cohorts has been conducted through data linkage with available hospital, mortality and cancer records. The evolution of asbestos-related disease has been recorded and, with the establishment of exposure measurements, quantitative exposure–response relationships have been estimated. There has been an ongoing epidemic of mortality from lung cancer and malignant mesothelioma and, less so, from asbestosis. Wittenoom crocidolite was used extensively in asbestos-cement products in Western Australia. As a result, the state has recorded a higher malignant-mesothelioma mortality rate than in any other Australian state and in any defined general population in the world. Thus, the legacy of Wittenoom has extended beyond the mine and the town, and is still evident more than 50 years after the closure of the mine.